2018
DOI: 10.1186/s12889-018-5653-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease (CVD) and associated risk factors among older adults in six low-and middle-income countries: results from SAGE Wave 1

Abstract: BackgroundCardiovascular disease (CVD) is one of the leading causes of death worldwide. Our study aimed to investigate the prevalence of two conditions, angina and stroke, and relevant risk factors among older adults in six low- and middle- income countries(LMICs).MethodsThe data was from World Health Organization (WHO) Study on global AGEing and adult Health (SAGE) Wave 1 in China, Ghana, India, Mexico, Russian Federation and South Africa. Presence of CVD was based on self-report of angina and stroke. Multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
133
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(142 citation statements)
references
References 32 publications
8
133
0
1
Order By: Relevance
“…In 2016, it was estimated that approximately 17.9 million people died from CVDs, representing 31% of all global deaths. At present, there is an estimate that this mortality rate will increase to more than 22.2 million by 2030 (Ruan et al, ). The most common causes of cardiovascular and circulatory deaths are continued to be the ischemic stroke, ischemic heart disease, hemorrhagic stroke, and heart failure (HF).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, it was estimated that approximately 17.9 million people died from CVDs, representing 31% of all global deaths. At present, there is an estimate that this mortality rate will increase to more than 22.2 million by 2030 (Ruan et al, ). The most common causes of cardiovascular and circulatory deaths are continued to be the ischemic stroke, ischemic heart disease, hemorrhagic stroke, and heart failure (HF).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown binge drinking and tobacco use increase the risk of NCDs 39 40. A study using data from the WHO Study on global AGEing and adult Health Wave 1 showed smoking and hypertension were both risk factors of stroke among older South African adults 41. South Africa is ranked as having one of the highest consumption rates of absolute alcohol per drinker per year 42.…”
Section: Discussionmentioning
confidence: 99%
“…Out of which myocardial infarction or heart attack (ischemic heart disease) is one the major contributor. It has been predicted that by the year 2030 more than 22 million people may die from CVDs (Ruan et al., 2018; Wilkins et al, 2017). Myocardial infarction is an acute condition occurred due to insufficient blood supply to the heart (cannot fulfill demand), it might be due to blockage in blood vessels (coronary artery) which in turn results in myocardial damage (enhance myocytolysis).…”
Section: Introductionmentioning
confidence: 99%